Istilah-Istilah Penamaan Tempat Wisata di Kawasan Gondang: Kajian Etnolinguistik - Tiwi Widya Lestari; Amelia Amanda Verawati; Adila Nisa Hamidah; Taswirul Afkar (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2025)
This study examines the naming of tourist attractions in Gondang District, Mojokerto Regency, through an ethnolinguistic approach to describe the meaning contained in the names. The object of study includes five tourist destinations, namely Akar Seribu, Bale Kambang, Kebun Pandansari, Padi Park, and Mbencirang Valley. This research used a descriptive qualitative method with data collection techniques in the form of field observations, interviews, and documentation. The data were analyzed using descriptive-interpretative analysis techniques, namely by describing the language form used in naming, interpreting the meaning based on the local cultural context, and linking it to the social and ecological functions of each area. The results of the study show that the naming of tourist attractions in this area not only functions as a geographical marker, but also as a representation of the community's relationship with nature, agrarian identity, and a form of language adaptation to changes in spatial functions.